2001
DOI: 10.1117/12.424383
|View full text |Cite
|
Sign up to set email alerts
|

<title>Cyclic fatigue of high-strength optical fibers in bending</title>

Abstract: Optical fiber may experience cyclic stresses at frequencies ranging from a few hertz in aerial cables to over a kilohertz due to vibration of machinery. The fatigue behavior of brittle materials typically gives times to failure that correspond to a suitably time-averaged applied stress and is independent of the frequency. Previous studies have been limited in the frequencies used but generally show agreement with this simple model. In this paper we describe results for the cyclic fatigue behavior of high stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Thus far, a number of studies showed that FBGs exhibit good durability under cyclic loading [13,14,57]. For instance, Matthewson et al [59] studied fatigue performance of the optical fibers (fused silica OF and acrylate coating) in bending at frequencies ranging from 0-100 Hz. They concluded that frequency of the cyclic loading has a minimal effect on the optical fiber in the specified stress range (up to the max load of 5050 MPa).…”
Section: Lifetime Of Fbgsmentioning
confidence: 99%
“…Thus far, a number of studies showed that FBGs exhibit good durability under cyclic loading [13,14,57]. For instance, Matthewson et al [59] studied fatigue performance of the optical fibers (fused silica OF and acrylate coating) in bending at frequencies ranging from 0-100 Hz. They concluded that frequency of the cyclic loading has a minimal effect on the optical fiber in the specified stress range (up to the max load of 5050 MPa).…”
Section: Lifetime Of Fbgsmentioning
confidence: 99%